Changing the Paradigm of Traditional Journalism to Digital Journalism: Impact on Professionalism and Journalism Credibility - Farid, Ahmad Salman (Journal International Dakwah and Communication, 2023)
The development of information technology and the internet has significantly transformed the landscape of media and journalism. Traditional journalism, which relied on print and electronic broadcasting, has evolved into digital journalism supported by online platforms. This change has had a profound impact on the professionalism and credibility of journalists. This research aims to analyze the paradigm shift from traditional journalism to digital journalism and explore its impact on journalistic professionalism and credibility. The methods used in this study are literature review and comparative analysis. In the literature review, we examine the relevant literature on the paradigm shift in journalism and its impact on journalistic professionalism and credibility. Comparative analysis is carried out by comparing the characteristics of traditional journalism and digital journalism and analyzing the changes that have occurred. The results of the study indicate that the paradigm shift from traditional journalism to digital journalism has changed the role of journalists in gathering, editing and delivering news. Digital journalism provides greater freedom and flexibility for journalists in creating content, but it also brings new challenges related to the validity and credibility of information. Journalists today are faced with demands to adapt to new technologies, master algorithms, and build a strong online presence. The results of the study indicate that the paradigm shift from traditional journalism to digital journalism has changed the role of journalists in gathering, editing and delivering news. Digital journalism provides greater freedom and flexibility for journalists in creating content, but it also brings new challenges related to the validity and credibility of information. Journalists today are faced with demands to adapt to new technologies, master algorithms, and build a strong online presence.